Pseudolagarobasidium baiyunshanense sp. nov. from China inferred from morphological and sequence analyses - Han, Mei-Ling; Bian, Lu-Sen; Zhang, Yuxin; Zhu, Mingcui; An, Qi (Phytotaxa, 2021)
A new species, Pseudolagarobasidium baiyunshanense, is described and illustrated based on morphological characters and molecular evidences. It is characterized by subcretaceous, odontioid to raduloid, white, grayish violet when fresh, cream, olivaceous buff when dry basidioma (at first deep olive in KOH then fading), short aculei (up to 1.8 mm long), monomitic hyphal system with clamped generative hyphae, ellipsoid to broadly ellipsoid basidiospores (4–6.1 × 2.9–3.9 µm). Phylogenetic analysis based on ITS+nLSU rRNA gene regions supported P. baiyunshanense as a distinctive species belonging to Pseudolagarobasidium.